Empowering Women in Aquaculture - Evidences from Jagatsinghpur, Odisha - Raja, Biswajit Sahoo; Sarita Das,; Gour Sundar Saha,; Abhijit Sinha Mahapatra,; Srichandan Das, (Indian Journal of Extension Education, 2023)
Empowerment levels of women involved in aquaculture-related vocations were measured using the Women Empowerment in Aquaculture Index (WEAI) in Jagatsinghpur, Odisha during 2022-23. Ninety-eight women belonging to 9 randomly chosen women self-help groups were studied using a structured interview schedule. Regression analysis indicated that 53.9 percent variation in the women empowerment level was attributed to annual income, information source utilization, social participation, participation in extension activity, training, and innovativeness. The empowerment level of 9 SHGs varied from 61-95 percent, with considerable differences between the domains- access to and control over resources and services, participation in social and economic activities, ability to make independent decisions, control over income usage, knowledge on aquaculture, and attitude towards aquaculture. Non-availability of bigger size fingerlings, lack of financial support from Govt. organizations, and lack of knowledge regarding recommended practices were among the constraints that limit women’s participation in aquaculture.